Komunikasi Visual dalam Sistem Informasi Lingkungan Digital untuk Meningkatkan Kesadaran Ekologi di Kalangan Masyarakat Medan Sunggal - Dybio Asih; Dede Tarigan; Jasael Simanullang (HK Publishing, 2026)
This study aims to understand how visual communication in digital environmental information systems contributes to the development of ecological awareness among the Medan Sunggal community. This study focuses on the phenomenon of communication of meaning construction through visual elements in digital platforms used to disseminate environmental information. A qualitative research design was used by conducting in-depth interviews with community members and analyzing the visual content of digital environmental information systems, including infographics, symbols, color usage, and visual narratives. Data were analyzed using thematic analysis to identify patterns in user interpretation, understanding, and perceived relevance of visual communication. The results show that visual elements that reflect local context, simplicity, and symbolic clarity play an important role in enhancing message comprehension and fostering ecological awareness. Digital environmental information systems function not only as information providers but also as communicative spaces where visual design mediates public understanding of environmental issues. This study is limited to a specific local environment and does not measure long-term behavioral outcomes, suggesting that future research should examine the impact of behavior or comparative cultural contexts. The originality of this study lies in its focus on local visual communication practices in digital environmental information systems, which offers valuable insights into applied communication strategies that integrate cultural context and visual meaning-making to support environmental awareness initiatives.